SYSTEMATIC LITERATURE REVIEW (SLR): PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) MATA PELAJARAN IPA DI SEKOLAH DASAR - Aldi Pramudya Baskoro; Rahadian Tri Harianti, Zulfa Cornelia, An Nisaa’ Sri Lestari, Fina Fakhriyah, Erik Aditia Ismaya (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Contextual Teaching and Learning is a learning concept that helps teachers relate the material taught to students' real-world situations and encourages students to make connections between the knowledge they have and its application in their lives as members of the family and society. This study aims to conduct a literature review related to the Contextual Teaching and Learning (CTL) learning model for science subjects in elementary schools. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research in the research report. The articles used in this study were 17 national journal articles obtained from the Google Scholar database using the Harzing's Publish or Perish application. Based on this research, it was found that the Contextual Teaching And Learning (CTL) learning model can make students have a good understanding and increase in learning outcomes in science subjects in elementary schools.